VIBRATION OPTIMIZATION AND CONTROL OF SEVEN-AXLE HYBRID COUPLING HYDRO-PNEUMATIC SUSPENSION VEHICLE - TIAN WenPeng; XIA Feng; XU XinXin (Jixie qiangdu)
In order to obtain the optimal vibration response of a seven-axle elevated platform vehicle with hydro-pneumatic suspension（HPS）, a hybrid coupling scheme of parallel connection ＆ contralateral cross-linked for HPS was designed. The dynamic model with 20 degrees of freedom which can comprehensively reflect vehicle coupling vibration including vertical-lateral-longitudinal-transverse was established. The vibration response characteristics of the vehicle and the influence of key parameters were analyzed by joint simulation. A single objective function contains two evaluation indices of vehicle ride comfort and stability was established through analytic hierarchy process（AHP） and range transformation standardization. The parameters optimization calculation of HPS was carried out. The model reference adaptive control, based on the principle of global vibration, applying Lyapunov design adaptive law, was carried on the HPS. The simulation results show that the evaluation index of vehicle vibration response is significantly improved after parameter optimization and superposition adaptive control.